Model of Islamic Religious Education Curriculum Reconstruction with a Global Perspective Based on an Integrative-Transformative Approach - Syarip Syarip; Fajri Ismail; Indah Wigati; Yuniar Yuniar; Feri Riski Dinata (CV. Bimbingan Belajar Assyfa, 2026)
This study is grounded in the challenges posed by globalization and the rapid acceleration of digital transformation, which necessitate the reconstruction of the Islamic Religious Education. curriculum to become more adaptive, contextual, and globally competitive. The existing Islamic Religious Education curriculum, which remains predominantly normative in orientation, has not yet fully succeeded in integrating 21st-century competencies with Islamic values in a comprehensive manner. Accordingly, this study aims to formulate a model for reconstructing a globally oriented Islamic Religious Education curriculum based on an integrative-transformative approach. This research employs a qualitative approach with a library research design, conducted through a critical review of relevant and up-to-date scholarly literature. Data were analyzed using content analysis and thematic analysis techniques to identify key concepts, patterns, and directions for curriculum development. The findings indicate that the reconstruction of the Islamic Religious Education curriculum should be carried out through the integration of Islamic values with global competencies, including critical thinking, creativity, communication, collaboration, and digital literacy. The proposed model comprises four main dimensions: value, global competence, pedagogical, and evaluative dimensions, all of which are implemented through an integrative-transformative approach. Therefore, the reconstructed Islamic Religious Education curriculum is expected to produce graduates who are not only religiously grounded but also adaptive and globally competitive